A pathway for protective quenching in antenna proteins of Photosystem II - Papadatos, Sotiris; Charalambous, Andreas; Daskalakis, Vangelis (My University, 2017)
Photosynthesis is common in nature, converting sunlight energy into proton motive force and reducing power. The increased spectral range absorption of light exerted by pigments (i.e. chlorophylls, Chls) within Light Harvesting Complexes (LHCs) proves an important advantage under low light conditions. However, in the exposure to excess light, oxidative damages and ultimately cell death can occur. A down-regulatory mechanism, thus, has been evolved (non-photochemical quenching, NPQ). The mechanistic details of its major component (qE) are missing at the atomic scale. The research herein, initiates on solid evidence from the current NPQ state of the art, and reveals a detailed atomistic view by large scale Molecular Dynamics, Metadynamics and ab initio Simulations. The results demonstrate a complete picture of an elaborate common molecular design. All probed antenna proteins (major LHCII from spinach-pea, CP29 from spinach) show striking plasticity in helix-D, under NPQ conditions. This induces changes in Qy bands in excitation and absorption spectra of the near-by pigment pair (Chl613-614) that could emerge as a new quenching site. Zeaxanthin enhances this plasticity (and possibly the quenching) even at milder NPQ conditions.
Keywords: Higher-plants; Green plants; Pigment Binding; Light Harvesting Complexes